KOMUNIKASI MATEN WELA PADA RITUAL KEMATIAN MASYARAKAT KEDANG NUSA TENGGARA TIMUR - Nurul Khasanah; Agus Subiyanto; Nurhayati Nurhayati (Prasasti: Journal of Linguistics)
This study is a qualitative descriptive study that discusses maten wela communication pattern in the death ceremony of the Kedang community in Lembata district, East Nusa Tenggara province. The focuses of the discussion are maten wela communication pattern and language stucture of maten wela.  The data was analyzed using the comparative linking technique "teknik hubung banding" initiated by Sudaryanto (2015). Data in the form of mantera then translated and strengthened by interviews with local community leaders. The theory used to describe data is the theory initiated by Hymes in (Troike; 2003). The results showed that the communication pattern of maten wela was divided into four sub-events, namely (1) before birang nutaq, (2) birang nutaq, (3) after birang nutaq, and (4) ka mema '. The structure pattern of mantera maten wela contains high politeness language, vowel-consonant patterns (n, o, n, ŋ, e, n, u, o, u) and consonant prefixes (n, n, m, b) and end with vowels (o, a, u, u).